2006
DOI: 10.1111/j.1752-1688.2006.tb04512.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Prediction Using Support Vector Machines

Abstract: Herein, a recently developed methodology, Support Vector Machines (SVMs), is presented and applied to the challenge of soil moisture prediction. Support Vector Machines are derived from statistical learning theory and can be used to predict a quantity forward in time based on training that uses past data, hence providing a statistically sound approach to solving inverse problems. The principal strength of SVMs lies in the fact that they employ Structural Risk Minimization (SRM) instead of Empirical Risk Minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
115
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(127 citation statements)
references
References 17 publications
0
115
0
Order By: Relevance
“…However, it inevitably suffers from the overfitting problem. Fortunately, some researchers reported the SVM method resolves the problem of overfitting encountered when analyzing high-dimensional data [36] and has been used to soil moisture [37], hourly typhoon rainfall [38], long-lead stream flows [39], leaf area index, and leaf chlorophyll density [40,41]. These studies have shown that the SVM approach is preferable to the ANN approach for these applications because of its greater generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…However, it inevitably suffers from the overfitting problem. Fortunately, some researchers reported the SVM method resolves the problem of overfitting encountered when analyzing high-dimensional data [36] and has been used to soil moisture [37], hourly typhoon rainfall [38], long-lead stream flows [39], leaf area index, and leaf chlorophyll density [40,41]. These studies have shown that the SVM approach is preferable to the ANN approach for these applications because of its greater generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…In using SVMs, an upper bound is minimized by the principle of structural risk minimization (SRM) whereas in using ANNs, traditional empirical risk minimization (ERM) is employed [30]. Recently, SVMs have been applied to estimate soil moisture [31], leaf area index, leaf chlorophyll density [32] and leaf infections [33].…”
Section: Introductionmentioning
confidence: 99%
“…This makes SVM a powerful tool for modeling the nonlinear complex environmental problems (Bhagwat and Maity 2012). Several studies reported the use of SVM in forecasting the soil water (Wu et al 2008), soil moisture prediction (Gill et al 2006), estimation of soil hydraulic parameters (Twarakavi et al 2009), modeling soil diffuse reflectance spectra (Rossel and Behrens 2010) and soil type classification (Kovačević et al 2010). Liao et al (2014) also used SVM, multiple stepwise regression (MSR) and ANN models to estimate the CEC from easily measured physicochemical properties (e.g., texture, soil organic matter, pH) based on 208 soil samples in Qingdao City, China.…”
Section: Introductionmentioning
confidence: 99%